(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
This study presents the design, construction and validation of the rubric “Acquisition of informal mathematical knowledge between 0 and 3 years old” (AIMK 0-3). In order to design and construct the rubric, a review has been carried out of the approach to evaluation set down in the first cycle of the Preschool Education curriculum, as well as the research available on informal mathematical knowledge before the age of 3. Eight experts in early childhood mathematics education in Spain have assessed the fitness, formulation and pertinence of the elements of the rubric. As a result of this assessment, some indicators and items have been incorporated, removed or modified in order to construct the definitive rubric, which aims to serve as both an evaluation tool and a guidance tool for Preschool teachers.